Desire and the ethics of advertising - Fuller, J (2016)
The aim of this thesis is to examine advertising from the point of view of Christian ethics: how it works, what is wrong with it and how it might go right as a practice. It argues that much existing criticism of advertising is justified, but that its power to create desire might be turned towards serving the good of the education of desire, leading us towards, or strengthening, a love of God, and helping us relate to products and services based on this love. This is significant because learning to desire well is central to living a Christian life, and because advertising influences how many people desire today. In contrast to authors who simply criticise advertising, often as part of a general critique of consumer culture, this thesis offers a constructive and detailed examination of the practice itself, looking at how its techniques work and how they might be reformed into an ‘art of advertising’. In making this argument the thesis draws primarily on Augustine, in addition to Plato, and modern critics of advertising. First, it describes desire, before examining how advertisements create desire, followed by an assessment of existing criticisms of this process. It then develops an account of the education of desire, identifying what an art of advertising should aim to achieve, before examining the techniques by which an advertisement might achieve this. The argument is intended to contribute to a project within Christian ethics of critiquing advertising, and presenting a workable ethical vision for the future of the industry.